The impact of the market knowledge to improve marketing performance an empirical study for mobil communication companies in iraq - جثير سعدون حمود; الشويلي حيدر عبد الواحد (Journal of Economics and Administrative Sciences, 2014)
The study aimed to determine the extent of market knowledge in the companies researched, as if market knowledge is qualified to lead the companies researched to achieve marketing performance , for this purpose, formulated hypotheses of the study in three hypotheses, the first major hypothesis "there is a correlation with significance of market knowledge to improve the marketing performance , "while the second major hypothesis, "there is a significant moral influence of market knowledge to improve the marketing performance " these hypotheses targeting to determine the role played by market knowledge in the leadership of companies researched to achieve improvement in marketing performance . And the study showed significant results for most stages of market knowledge to improving the marketing performance , as well as the study reached the existence of significant differences between the companies researched the level of market knowledge to improve the marketing performance , and led the results of the practical side of the study on a number of conclusions was the most prominent of which contribute to the market knowledge that makes the organization more able to achieve the improvement of the marketing performance and dominating the target markets, as well as the existence of significant differences between the two companies researched the level of market knowledge to improve the marketing performance .